2011
DOI: 10.1111/j.1600-6143.2010.03405.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional Cytomegalovirus-Specific Immunity in Lung Transplant Recipients Receiving Valganciclovir Prophylaxis

Abstract: †Palmer and Weinhold contributed equally to the manuscript.Cytomegalovirus (CMV) is a common opportunistic infection after lung transplant. Despite effective antiviral medications to treat CMV, invasive CMV disease contributes to lung allograft dysfunction and worse survival. Efforts to prevent CMV have led to the use of valganciclovir prophylaxis for increasingly longer periods after transplant. A pivotal concern with long-term antiviral prophylaxis is that it may prevent or delay the development of CMV-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…In particular, we observed that, in a small fraction of four R+ LuTRs, high-level HCMC DNAemia occurred in spite of stable responses. In the control of HCMV replication, the importance of CD8+ T cell specificity, that is, the spectrum of viral proteins to which responses are directed, has been highlighted previously (21,23,(28)(29)(30)(31). Furthermore, it has been demonstrated that virus-specific CD4+ T helper cells are necessary for the generation and maintenance of CD8+ T cells (24,28,(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we observed that, in a small fraction of four R+ LuTRs, high-level HCMC DNAemia occurred in spite of stable responses. In the control of HCMV replication, the importance of CD8+ T cell specificity, that is, the spectrum of viral proteins to which responses are directed, has been highlighted previously (21,23,(28)(29)(30)(31). Furthermore, it has been demonstrated that virus-specific CD4+ T helper cells are necessary for the generation and maintenance of CD8+ T cells (24,28,(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…In the control of HCMV replication, the importance of CD8+ T cell specificity, that is, the spectrum of viral proteins to which responses are directed, has been highlighted previously (21,23,(28)(29)(30)(31). Furthermore, it has been demonstrated that virus-specific CD4+ T helper cells are necessary for the generation and maintenance of CD8+ T cells (24,28,(30)(31)(32)(33). The QuantiFERON R -CMV assay (Cellestis GmbH, a QIAGEN company) is designed to stimulate CD8+ T cells specifically with a mixture of multiple HCMV peptides and therefore does not allow the specific targeted epitope to be identified or CD4+ T cell functionality to be evaluated (25,34).…”
Section: Discussionmentioning
confidence: 99%
“…Details of sample collection and storage of peripheral blood mononuclear cells have been previously published and are also provided in the online supplement (9).…”
Section: Sample Collection and Storage Of Peripheral Blood Mononucleamentioning
confidence: 99%
“…Compensation beads were used, and data were acquired immediately with a LSRII flow cytometer (Becton-Dickinson, San Jose, CA). Additional details of the methods to assess CMV-specific immunity and gating strategy are provided in the online supplement, are displayed in Figure 1, and have been previously published (9).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation